Focusing on surgery results in infertile patients with deep endometriosis. (3rd August 2015) - Angioni, Stefano; Cela, Vito; Sedda, Federica; Stochino Loi, Emanuela; Cofelice, Vito; Pontis, Alessandro; Melis, Gian Benedetto
Abstract: Infertility is a common problem in patients with endometriosis and the involved mechanisms are still not completely known. The management of infertility in endometriosis patients includes surgery as well as assisted reproductive technology. Laparoscopic surgery has shown better results in infertility patients with endometriosis in comparison to laparotomy procedures. Laparoscopic surgery has proposed benefits in both minimal to moderate diseases. However, while there may be some benefits with severe diseases, there is still not enough evidence to recommend laparoscopic surgery as the recommended surgery when the main goal is to obtain fertility. We performed a MEDLINE search for articles on fertility in women with deep infiltrating endometriosis (DIE) published between 1990 and April 2015 using the following keywords: "endometriosis", "deep infiltrative endometriosis", "infertility", "fertility after surgery", "laparoscopy surgery", "laparotomy", "pregnancy", "fertility outcome", "bladder endometriosis", and "ureteral endometriosis". The aim of this review was to analyze the results of available clinical studies (randomized controlled or not controlled studies; retrospective cohort studies; or case–control and prospective studies) and guidelines on surgical treatment of infertile endometriosis patients, and pregnancy outcomes after surgery. Chinese abstract: 不孕症是子宫内膜异位症患者很常见的问题，其涉及到的机制并没有被完全了解。子宫内膜异位中的不孕患者的治疗方法包括手术和辅助生殖技术。在子宫内膜异位导致的不孕患者中，腹腔镜手术比开腹手术越来越显示出更好的结局。腹腔镜手术在某些最小及中度疾病中有优势而被推荐。虽然，腹腔镜手术在某些疾病的治疗中有优势，然而当主要目标是使患者获得生育时，依旧没有足够的证据使得腹腔镜作为推荐的标准治疗方式。我们实施了一项文献检索，搜索了1990年-2015年4月间发表的以"子宫内膜异位症""深浸润子宫内膜异位症"、"不孕症"、"手术后生育"、"腹腔镜手术"、"开腹手术"、"妊娠"、"生育结局"、"膀胱子宫内膜异位症"、"输尿管子宫内膜异位症"为关键词的与女性生育能力和深浸润子宫内膜异位的相关的文章。这篇综述的目的是分析现有的临床研究的结果（随机对照研究和非随机情况下的对照研究；回归性队列研究；病例对照和前瞻性研究）、子宫内膜异位症所致不孕症的外科治疗的指南以及手术后的妊娠结局。